Transformasi Pendidikan Dalam Meningkatkan Literasi Digital Bagi Pendidik dan Pelajar di Indonesia - Zulfa Ishmah Rahadatul Aisy; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
The transformation of education through the use of digital media has had a significant impact on the world of education. This encourages increasing digital literacy as an important role in facing the digital era. Digital literacy can improve access to information, critical thinking skills, learning quality, competitiveness and national progress. Education in Indonesia is currently facing special challenges in managing rapid changes in times. To increase digital literacy, increased training programs, sharing of experiences and further research are needed. There are eight basic elements in developing digital literacy, namely cultural, cognitive, constructive, communicative, self-confident, creative, critical and responsible. This research uses a qualitative approach with a literature study method. The literature study research method involves a thorough analysis of relevant literature and information sources by collecting data from books, scientific journals, articles, and other sources, then analyzing, evaluating, and synthesizing the information obtained to prepare a comprehensive argument or summary. Qualitative research is descriptive and tends to use inductive analysis, so that processes and meaning based on the subject's point of view are emphasized more in this qualitative research. This qualitative research design can be used as a research method because it is explained comprehensively and is easy for researchers to understand. This research aims to determine the effect of educational transformation by increasing digital literacy among Indonesian society.